Brewer's spent grain pyrolysis kinetics and evolved gas analysis for the sustainable phenolic compounds and fatty acids recovery potential. (November 2022) - Sobek, S.; Zeng, K.; Werle, S.; Junga, R.; Sajdak, M.
Abstract: Within the presented paper, a thermochemical conversion via pyrolysis of spent grain from the local brewery (Alternatywa, Ruda Śląska, Poland) for phenolic compounds and fatty acids recovery is presented. Thermogravimetric pyrolysis was carried out at non-isothermal conditions (1, 2, and 4 K/min), under an inert N2 atmosphere. Deconvolution procedure for the kinetic modeling was implemented using own algorithm based on Gaussian function, using 3-stage kinetic mechanism, ascribed to the independent decomposition of the pseudo-components i.e., hemicellulose, cellulose, and bulk lignin-extractives. Released volatiles during pyrolysis was evaluated and recognized using gas chromatography-mass spectrometry and Fourier-transform infrared spectroscopy analysis, which confirmed the high content of fatty acids, phenolic compounds, and nitrogen compounds, with shares of 23.95%, 13.94%, and 25.10% respectively. Linkage of the desired product formations to the modeled kinetic stages of the BSG pyrolysis is a complex subject, and it is encouraged for future studies. Graphical abstract: Image 1 Highlights: BSG pyrolysis resulted in high shares of phenolics and fatty acids in the products. 3 stage kinetic model of BSG pyrolysis based on Gaussian deconvolution is presented. Isoconversional Eα varied from 44 to 228 kJ/mol showing complex decomposition pattern. BSG pyrolysis was investigated at TGA and GC-MS FTIR method at low heating rates. Kinetic computations were validated through kinetic predictions.